Investigating Culturally Responsive Practices: Perceptions and Experiences of Secondary School Middle Leaders - Morgan, Leigh (Auckland University of Technology, 2017)
The aim of this research was to critically examine the perceptions and understandings of culturally responsive practices carried out by secondary school middle leaders in low decile, multi-ethnic school settings in New Zealand. Semi-structured interviews were conducted with seven middle leaders from six different secondary schools in the Auckland region. Middle leaders’ understandings, experiences and challenges that they encountered in their schools were diverse and multi-faceted. The data revealed that culturally responsive leadership is influenced by personal, interpersonal and school factors. Possessing personal traits that allowed middle leaders to be innately culturally responsive, and which allowed them to effectively communicate and form learning and working relationships, were considered to be the most influential factors in effective culturally responsive middle leadership. The redesigned socio-ecological model presented in this thesis acknowledges the importance of both culturally responsive practices and culturally responsive leadership by middle leaders. A number of recommendations arose from this research. Culturally responsive leadership and practices involve a committed approach from principals, senior management, middle leaders and teachers to engage students and families in the community. Individual teachers need to critically reflect on their personal values and beliefs and how these might influence their teaching practices. The research also highlighted the importance of emphasising both bi-culturalism and multiculturalism if schools are to meet their obligations to Te Tiriti o Waitangi.
Keywords: culturally responsive practices; qualitative methodology; semi-structured interviews; secondary school; middle leaders; educational leadership